Gender representation in Indonesian primary English textbook: A corpus and micro-semiotic analysis - Rena Kinanti Amirulloh; Nunung Suryati (Universitas Tidar, 2026)
The pattern of gender bias that has been circulating in the textbooks shows nearly identical patterns, which still reinforce traditional norms and expectations. Meanwhile, English Foreign Language (EFL) Textbooks can influence learners’ beliefs about appropriate roles and actions for each gender by reinforcing cultural norms and expectations. Many studies on gender in English textbooks at all levels of Indonesian education have been conducted. However, only a few studies examine gender representation in Indonesian primary English textbooks used in the current curriculum. Addressing this gap, the present study integrates corpus and micro semiotic analysis to examine how gender is portrayed in the Primary EFL Textbook used in the Merdeka Curriculum for Grade 6, titled My Next Words. This research aims to analyze the textual and visual representation of gender bias embedded in the selected textbook. The result of this research indicates that although the author of the textbook has tried to balance gender visibility and representation, subtle disparities remain, with 9% difference. Furthermore, the findings show that males are more closely associated with physical, authoritative, and outdoor activities, while females are more closely associated with domestic, caring, and indoor-oriented roles. The textbook's imbalanced representation leads to unequal opportunities for men and women. To address this, inclusive materials that provide equal opportunities are needed.